A novel ram-air plasma synthetic jet actuator for near space high-speed flow control. (April 2017) - Zhou, Yan; Xia, Zhixun; Luo, Zhenbing; Wang, Lin; Deng, Xiong
Abstract: As a promising high-speed flow control technique, plasma synthetic jet actuator (PSJA) has the superiorities of requiring no moving parts or flow supplies, extremely fast response, wide frequency band and high efflux speed. However, it has limitations for application: in near space, the air in the cavity which is used to generate the puled plasma jet becomes rare, and the low refill rate often leads to insufficient recovery which limits the working frequency. In order to overcome these limitations, a novel actuator called ram-air plasma synthetic jet actuator (RPSJA) is proposed. Inspired by the ramjet, the principle of this actuator is to take advantage of the tremendous dynamic pressure of the high-speed inflow using an added ram-air inlet. Numerical investigations were conducted to demonstrate the feasibility of such an actuator. The results show that, compared with PSJA, the air in the chamber becomes denser and the refill rate is notably increased owing to the "ram-air effect" of RPSJA. Based on the flow characteristic analysis, a revised actuator with a stepped ram-air inlet is proposed and investigated as well, and the results show that the performance is improved as the stepped height rises. Highlights: A novel ram-air plasma synthetic actuator (RPSJA) is proposed. Contrastive study of RPSJA and traditional plasma synthetic actuator is conducted. RPSJA has better adaptability to near space and high-frequency working condition. A revised RPSJA with a stepped ram-air inlet is proposed.